Bibliometric Analysis of Islamic Banking Literature Published in Times of Covid-19 Pandemic - Muhammad Raihan Gunawan; Aam Slamet Rusydiana (University of Darussalam Gontor, 2022)
This study aims to analyze articles with the subject matter of Islamic Banking published during the 2020-2021 period in times of the Covid-19 Pandemic and indexed by Scopus (https://scopus.com) on an analysis of articles, authors, journals, and keywords. The papers analyzed were as many as 681 documents using bibliometric analysis with the help of R Biblioshiny software. The numbers showed the researcher's high desire to research with the theme of Islamic Banking during the pandemic. The author who often studies this theme is Hassan MK. Most journals published on Islamic Banking during covid-19 are